Concurrent strength and interval endurance training in elite water polo players - Botonis, P. G.; Toubekis, A. G.; Platanou, T. I. (The Journal of Strength and Conditioning Research, 2016)
This study compared the effects of different high-intensity interval training (HIIT) intervals performed concurrently with strength and specific water polo training on performance indices of elite players. During the precompetition season, 2 water polo clubs were assigned to either HIIT of 4 × 4 minutes (n = 7, HIIT4 × 4) or HIIT of 16 × 100-m swimming efforts (n = 7, HIIT16 × 100). Both clubs applied the swimming (6% above the speed corresponding to blood lactate concentration of 4.0 mmol/L) and strength training (85-90% of 1 repetition maximum, 5 repetitions, 4 sets) twice per week concurrently with specific water polo training. Before and after the 8-week intervention period, maximal bench press strength was measured and a speed-lactate test (5 × 200 m) was performed to determine the speed corresponding to lactate concentration of 4.0, 5.0, and 10.0 mmol/L. Maximal strength was improved in both groups (HIIT4 × 4: 14 ± 4% vs. HIIT16 × 100: 19 ± 10%). Improvements in speed corresponding to 4.0, 5.0, and 10.0 mmol/L were shown only after HIIT4 × 4 (9 ± 5, 8 ± 3, 7 ± 2%, respectively; p < 0.01). However, HIIT16 × 100 was more effective in the differential velocity between 10.0 and 5.0 mmol/L development (19 ± 20%, p = 0.03). During the precompetition season, HIIT and strength training together with specific water polo training performed concurrently improves muscle strength and allows specific adaptations enhancing swimming performance of elite water polo players